Marcas autoriales de composición en fray Antonio de Guevara: compositio numerorum y enumeraciones (más o menos) fraudulentas - Emilio Blanco (Atalaya)
This article gives an account of the extraordinary frequency with which Antonio de Guevara, in his Dial of Princes, resorts to numeric patterns inorder to organise the course of his prose. After a review of the classicaland patristic intellectual framework that could encourage that rhetoricalpractice, we aim to prove that this is another authoritative resource,together with the quotation of classical authorities, so as to insert intothe tenuous argument –the life of the Roman Emperor Marcus Aurelius– the doctrine he wants to communicate to his audience.